Susceptibility Polymorphism in the Promoter Region of IL-4 and IL-13 in Individuals with Periodontitis: A Systematic Review - Silva, Rafaella Ugrin de Oliveira; Longhi, Maria Tereza de Moraes; Caldeira, François Isnaldo Dias [UNESP]; Silva, Renata Cristina Lima [UNESP]; Alvitos, Rodrigo; Fernandes, Leandro Araújo; Lima, Catarina Pereira Monteiro [UNESP]; Capote, Ticiana Sidorenko de Oliveira [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: To understand the susceptibility to single nucleotide polymorphisms in the promoter region of Interleukin-4 (IL-4) and Interleukin-13 (IL-13) in patients with and without periodontal disease. Thus, a systematic review of available studies on the subject was performed. Material and Methods: A protocol was conducted for registration in the International Prospective Register of Systematic Reviews (PROSPERO) under CRD42021246646. For this search, studies were selected from the Scopus, Web of Science, Virtual Health Library, Embase, Cochrane Library, and PubMed databases. The selection criteria consisted of case-control and cohort studies published in English that had data on IL-4 and IL-13 genetic polymorphisms in patients with and without periodontal disease in the same study. The obtained studies were managed by EndNote Program™ X7 version and the Rayyan Platform. Regarding the risk of bias, we used the Newcastle-Ottawa Scale, which classified the studies using high-quality methodology. Results: After the selection process, three studies presented the eligibility criteria. No relation between IL-13 and susceptibility to periodontal disease was found. IL-4 gene (IL-4-590C/T; IL-4-34C/T; rs2243248) was associated with susceptibility to the development of periodontitis. Conclusion: An association between IL-4 and the susceptibility of periodontitis was verified. Further case-control studies are needed to create more concrete conclusions on the subject.
Keywords: Genetic; Periodontitis; Polymorphism; Review